2010
DOI: 10.1080/02699930802584466
|View full text |Cite
|
Sign up to set email alerts
|

Restore and protect motivations following shame

Abstract: Shame has been found to promote both approach and withdrawal behaviours. Shame theories have not been able to explain how shame can promote such contrasting behaviours. In the present article, the authors provide an explanation for this. Shame was hypothesised to activate approach behaviours to restore the threatened self, and in situations when this is not possible or too risky, to activate withdrawal behaviours to protect the self from further damage. Five studies with different shame inductions and differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
154
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(171 citation statements)
references
References 43 publications
12
154
0
5
Order By: Relevance
“…It is possible that shame motivates social approach when such interactions are neutral to or positive for the damaged self, but that shame motivates social withdrawal when interactions would further harm the damaged self. This converges with recent findings that shame motivates restoration of the damaged self, but that this restore motive decreases when situational factors make it too risky or difficult to restore (De Hooge et al, 2010. Neither of our studies were specifically designed to address these issues, so it might be interesting to address these in subsequent, more targeted research.…”
Section: Limitationssupporting
confidence: 56%
See 1 more Smart Citation
“…It is possible that shame motivates social approach when such interactions are neutral to or positive for the damaged self, but that shame motivates social withdrawal when interactions would further harm the damaged self. This converges with recent findings that shame motivates restoration of the damaged self, but that this restore motive decreases when situational factors make it too risky or difficult to restore (De Hooge et al, 2010. Neither of our studies were specifically designed to address these issues, so it might be interesting to address these in subsequent, more targeted research.…”
Section: Limitationssupporting
confidence: 56%
“…Interestingly, a recent line of research has focussed on the potential positive consequences of shame, suggesting that it would motivate positive interpersonal behaviours to restore one's threatened self (De Hooge, Zeelenberg, & Breugelmans, 2010. Indeed, empirical research has repeatedly demonstrated shame to be able to induce prosocial behaviours, such as donating, cooperating, or gift giving, notably in situations where people are together with others towards whom they feel ashamed (De Hooge, 2014;De Hooge, Breugelmans, & Zeelenberg, 2008).…”
mentioning
confidence: 99%
“…Further, they have found that shame activates an approach motivation when it appears to be possible, and not too risky, to affirm and restore a positive self-view [87,88]. Along these lines, Leach and Cidam found in their meta-analysis that the single best predictor of an individual having a constructive approach orientation after a shame episode was the degree to which the failure was more reparable [53].…”
Section: Guilt and Shame Action Tendencies And Appraisalsmentioning
confidence: 99%
“…Decomposing shame-proneness, we expect NSEs to deter self-forgiveness directly (as painful self-focused cognitions facilitate negative selfdirected reactions) and indirectly (as people respond to NSEs by withdrawing). However, given that shame has been inconsistently associated with both decreased (Howell et al, 2012) and increased de Hooge et al, 2010) repair-type responses, it is unclear whether repair may play a clear mediating role. The mediational prediction is depicted in Figure 1. …”
Section: Role Of Shame-proneness In Self-forgivenessmentioning
confidence: 99%
“…Conversely, shame is associated with offenders' attempts to protect self-images (Tangney & Dearing, 2002). This includes avoidance (e.g., withdrawal, secrecy; DeLong & Kahn, 2014;Yi, 2012) as well as behavior change (but only when doing so mitigates self-image threat; de Hooge, Zeelenberg, & Breugelmans, 2010).…”
Section: Guilt-and Shame-pronenessmentioning
confidence: 99%